Peran Kreativitas dan Inovasi dalam Meningkatkan Daya Saing UMKM: Studi Kasus Shiflow Kota Medan - Zendrato, Peter Juliyaman; Lubis, Nurul Wardani; Rajagukguk, Narda Kalyana; Nainggolan, Agustina; Rani, Dinda Annisa (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine and analyze the role of innovation and creativity in increasing the competitiveness of the Shiflow business in the city of Medan. The data collection technique used was a survey. This technique refers to the use of questionnaires or questionnaires to collect information from respondents who represent the population or sample you are researching. Data analysis uses correlation analysis, namely determining whether there is a statistical relationship between two or more variables. In this research there are simple linear regression analysis which contains classical assumption tests and hypothesis testing in the form of the coefficient of determination (r) and partial test (t test). The research results show that innovation has a significant effect on increasing competitiveness. This is shown based on the results of the t test, namely the Innovation variable with a significance value of 0.001 < 0.05 so it can be concluded that hypothesis 1 (H1) is accepted. Creativity does not have a significant effect on increasing competitiveness. This is shown based on the results of the t test, namely the creativity variable with a significance value of 0.029 > 0.05 so it can be concluded that hypothesis 2 (H2) is rejected.